2012
DOI: 10.1259/bjr/27844842
|View full text |Cite
|
Sign up to set email alerts
|

Which should be the routine cross-sectional reconstruction mode in spectral CT imaging: monochromatic or polychromatic?

Abstract: Objective: To provide evidence for the selection of an optimal cross-sectional reconstruction mode in spectral CT imaging of the abdomen, we compared the monochromatic images with polychromatic images. Methods: Three phase-enhanced CT scans of the abdomen were recorded using the spectral imaging technique on 100 patients. Images were reconstructed using two modes: polychromatic and 70 keV monochromatic. The following variables were then compared: contrast-to-noise ratio (CNR) of the liver, spleen, gallbladder,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…However, previous studies using early DE-VM algorithms have shown that high-contrast, low-monoenergetic-energy images that contain increased iodine signal also contain higher levels of image noise [4, 5]. This significant noise burden at lower energies has been a limiting factor in the clinical application of virtual monoenergetic imaging.…”
mentioning
confidence: 99%
“…However, previous studies using early DE-VM algorithms have shown that high-contrast, low-monoenergetic-energy images that contain increased iodine signal also contain higher levels of image noise [4, 5]. This significant noise burden at lower energies has been a limiting factor in the clinical application of virtual monoenergetic imaging.…”
mentioning
confidence: 99%
“…6). Previous studies showed that liver imaging was able to benefit by monochromatic extrapolation of CT images [16,17] in terms of increased sensitivity for the detection of lesions and greater diagnostic confidence [17]. Nevertheless, 70 keV was recommended due to increased noise levels to achieve the best overall image quality [15,17].…”
mentioning
confidence: 99%
“…On the other hand, dual energy spectral CT imaging generates a set of virtual monochromatic images through the material decomposition process enabled by the use of the information from the two energy spectra of high and low kVp projections. The use of a monochromatic X-ray beam in CT would greatly reduce the averaging attenuation effect and increases contrast resolution[ 13 ]. The generation of virtual monochromatic image sets of various energy levels, especially low photon energy images in spectral CT imaging also allows us to select the optimal energy level to maximize the contrast-to-noise ratio for bronchial arteries in contrast-enhanced CT scans.…”
Section: Discussionmentioning
confidence: 99%